Looking for "in-between" Places - Manuel Portela; Albert Acedo; Carlos Granell-Canut (Media Theory)
This article develops the concept of "in-between" places in relation to the study of language, perceptions and memories within the broader mediation of cartography. We held an empirical qualitative study in the city of Lisbon, Portugal, where a group of participants (1) performed a web map-survey to identify the spatial dimensions of their sense of place, (2) had a joint discussion about the representations and memories associated with their chosen places, and, finally, (3) took a go-along walk to obtain a deeper definition and characterization of them. Results suggest that analog and digital maps generate different virtual images of space, while the navigational use of digital maps in particular generates multiple representations of the territory. The mediation of different narrations and the description of encounters within the Person-Place-Process triad helped us to establish the importance of in-between places for a complete conceptualization of place.